Efectos del movimiento en la tasa de cambio sobre la balanza comercial durante el periodo 1994-2015 en Colombia (2016)
"This document aims to test if the Exchange rate movement has effects over the Colombian trade balance during the period 1994 ? 2015. By estimating ordinary least squares model with different functional forms for the trade balance, exports and imports is possible to find out that the exchange rate has a clear effect over the trade balance behavior as long as time lags are included within the model for the last three quarters. Within this framework, is possible to see that when imports increase, exports decrease and viceversa having always into account that the exchange rate represents one of the adjustment and connection channels between both variables." -- Tomado del Formato de Documento de Grado.